A forma na paisagem: a observação dos projetos Praça das Artes (SP, 2012) e Museu do Amanhã (RJ, 2015) - KULAIF, Patricia Marcucci (2017)
This dissertation observes the urban landscape in its form, since it can interfere in the perception and experience of inhabitants in contemporary cities. Two projects have been selected: the Praça das Artes Building, in São Paulo, with part of its construction concluded in 2012, and the Museu do Amanhã, located in Rio de Janeiro, finished in 2015. Both buildings are located in areas of Urban Operation determined by the municipalities, and were built after the 2000s, aiming to meet the needs of the population and revitalize central areas. To study them, field researches were carried out, as well as informal interviews, and reflections on themes addressed by authors such as Lynch, Peixoto, Zonno and Gehl on the city dynamics and the development of the landscape. The shape created and its reactions were discussed. So were observations on its design according to Flusser, Denis and Ching, the perception approach in Merleau-Ponty and Bachelard, and the space according to Massey and Krauss. It then becomes possible to understand how these architectural structures and individuals behave in their surroundings, interacting with the visuality created and forming a "living city" to some extent.